The effectiveness of TGT learning assisted by wordwall media on student mathematics learning motivation - Rahmatussolihah, Irkhas Tri; Wilisati, Rani Septi; Putri, Alfina Rifky Taftiana; Dewi, Etika Chandra; Sadieda, Lisanul Uswah; Rahayu, Dika Sari (Institute of Computer Science (IOCS), 2024)
The use of media in learning that is not appropriate will cause boredom for students so that learning will seem monotonous and affect students' motivation to learn mathematics. This study aims to determine the effectiveness of TGT (Teams Games Tournamet) learning assisted by Wordwall media on students' math learning motivation. This research is included in the experimental research of one group posttest-only design. The subjects of this study were students of class VII-A SMP Negeri 2 Waru as many as 31 students. The results showed that the learning motivation of students in class VII-A SMP Negeri 2 Waru in the 2023/2024 school year after being given treatment was in the